2021
DOI: 10.3390/ijms22052237
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis HmuY and Bacteroides vulgatus Bvu—A Novel Competitive Heme Acquisition Strategy

Abstract: Human oral and gut microbiomes are crucial for maintenance of homeostasis in the human body. Porphyromonas gingivalis, the key etiologic agent of chronic periodontitis, can cause dysbiosis in the mouth and gut, which results in local and systemic infectious inflammatory diseases. Our previous work resulted in extensive biochemical and functional characterization of one of the major P. gingivalis heme acquisition systems (Hmu), with the leading role played by the HmuY hemophore-like protein. We continued our st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 56 publications
6
36
0
Order By: Relevance
“…HmuY is the first and best characterized representative of a novel family of bacterial hemophore-like proteins, distinct from a family of classical secreted hemophores [ 16 , 30 ]. Previously, we performed detailed phylogenetic analyses [ 24 , 25 , 26 , 27 , 28 ], which demonstrated that although the proteins forming this unique family are phylogenetically related and structurally similar, differences in amino acid sequences ( Figure 1 ) could result in different structure of heme-binding pockets ( Figure 2 ). The independent evolution of heme binding resulted in different mechanisms of heme coordination in HmuY (two histidine residues) compared to its homologs characterized so far (two methionine residues).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…HmuY is the first and best characterized representative of a novel family of bacterial hemophore-like proteins, distinct from a family of classical secreted hemophores [ 16 , 30 ]. Previously, we performed detailed phylogenetic analyses [ 24 , 25 , 26 , 27 , 28 ], which demonstrated that although the proteins forming this unique family are phylogenetically related and structurally similar, differences in amino acid sequences ( Figure 1 ) could result in different structure of heme-binding pockets ( Figure 2 ). The independent evolution of heme binding resulted in different mechanisms of heme coordination in HmuY (two histidine residues) compared to its homologs characterized so far (two methionine residues).…”
Section: Resultsmentioning
confidence: 99%
“…Our theoretical and experimental analyses identified homologs of P. gingivalis HmuY in other bacteria [ 24 , 25 , 26 , 27 , 28 ]. In general, the identity of amino acid sequences of these proteins is rather low.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations